Modulation of growth performance, immunological responses and disease resistance of juvenile Nile tilapia ( Oreochromis niloticus ) (Linnaeus, 1758) by supplementing dietary inosine monophosphate - Kader, Md. Abdul; Bulbul, Mahbuba; Abol-Munafi, Ambok Bolong; Asaduzzaman, Md.; Mian, Sohel; Noordin, Noordiyana Mat; Ali, Md. Eaqub; Hossain, Md. Sakhawat; Koshio, Shunsuke (Elsevier, 2018)
This study was investigated to examine supplemental effects of dietary inosine monophosphate (IMP) on growth performance, feed utilization, biochemical, hematological and immunological parameters of juvenile Nile tilapia Oreochromis niloticus. Disease resistance to experimental infection with Streptococcus agalactiae was also assessed. A semi-purified basal diet was supplemented with 0 (IMP0, Control), 1 (IMP1), 2 (IMP2), 4 (IMP4) and 8 (IMP8) g purified IMP kg−1 diet to formulate five experimental diets. Each diet was randomly allocated to triplicate groups of fish (0.59 g) for 60 days. The results indicated that supplementation of IMP significantly (P < 0.05) improved growth performances of fish. The highest final weight was found in IMP2 followed by IMP8, IMP4 and IMP1. Feed utilization parameters were also positively influenced by dietary IMP supplementation and IMP2 supplemented group showed improved values. Feed intake increased with dietary IMP supplementations but not at a significant level (P > 0.05). Among whole body proximate composition and somatic parameters, condition factor was significantly influenced by dietary supplementation of IMP. A wide variation in hematological parameters were observed and dietary supplementation increased the hematocrit content (P < 0.05) and red blood cells (P > 0.05). Total serum protein (TSP), lysozyme activity (LA), superoxide dismutase activity (SOD) and bactericidal activity (BA) tended to increase with the supplementation of dietary IMP. TSP and SOD were significantly improved with ≥4 g kg−1 supplementation, while LA with 8 g kg−1 and BA with ≥1 g kg−1 supplementations. IMP supplemented groups showed higher (P > 0.05) cumulative survival compared to that of supplementation free control group. IMP supplemented diet groups also showed significantly higher BA in the post challenge test. Based on the overall performances, the results of the current study indicated that the inclusion of IMP in Nile tilapia diet can improve growth performance, feed utilization, haematological and immunological parameters; and disease resistance of juvenile Nile tilapia.